Analisis Kesalahan Berbahasa Indonesia dalam Menulis Surat Dinas pada Siswa Kelas VII SMPN 2 Tasikmalaya (International Forum of Researchers and Lecturers, 2024)
This research was conducted using descriptive research methods. The research was conducted in class VII of SMPN 2 Tasikmalaya with the aim of finding out errors in Indonesian in official letters. Middle school students must be able to master writing skills, one of which is writing official letters. The research results obtained were that there were language errors at the levels of phonology, morphology, syntax and semantics. This is caused by students' lack of mastery and mastery of Indonesian and the influence of the habit of using their mother tongue or first language. Therefore, students need motivation and awareness to be able to improve their official letter writing skills. Apart from that, there is a need for directed attention and guidance from the teacher.